The impact of human capital management practices on employee motivation and work efficiency among employees in Hi-Tech Enterprises in China - Dong, Jia Yuan (2007)
Employee motivation and work efficiency is very important with an organization. The objective of this research is to examine whether human capital management practices (compensation, supervisor, training, and employee relations) have a positive impact on employee motivation, whether employee motivation and work efficiency have a significantly relationship, whether employee motivation plays a role in intervening the relationship between human capital management practices and work efficiency, and whether age and job experience play moderate roles in the relationship between human capital management practices and employee motivation and the relationship between employee motivation and work efficiency. The literature review provides detail development of how these variables influence employee motivation and work efficiency. The respondents were based on randomly selected. The questionnaires were constructed out of extensive literature review. The hypotheses were tested using SPSS program of simple regression, multiple regression and hierarchical regression. The research discovered that human capital management practices (compensation, supervisor, training, and employee relations) have a positive impact on employee motivation, there is a significantly between employee motivation and work efficiency, employee motivation plays an intervening role between human capital management practices and work efficiency, and age and job experience do not play moderate roles in the relationship between human capital management practices and employee motivation and the relationship between employee motivation and work efficiency.